The effect of 2366 meter altitude training on swimmers physiological function and performance - Ma, F.; Fan, R.; Qi, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Chinese swimmers adopted altitude training early (at 1900 m Kunming) above sea level and the national swimming team first used altitude training at Duoba, Qinghai (2366 m) for 26 days in 2006. The present study aims to reveal the effects of 2366m altitude training on swimmers` physiological function and performance through the measurement of a range of physiological and biochemical indices. Methods Members of the Chinese National swimming team including 13 males and 21 females acted as subjects in this study. Routine physiological and biochemical measurements were taken at different times pre and during the training period including : (blood; RBC, Hb, HCT, WBC, MCV l.), blood urea (BUN), arterial oxygen saturation (SaO2), testosterone (T), urine index (PRO, URO, et al), creatine kinase (CK), body weight (W), blood lactic acid (Bla) and heart rate (HR). Test instruments included: Chemiluminescence immune assay analysator (Backman Coulter, USA), semi-automatic biochemistry analysator (Eppendorf6124, German), blood lactic acid analysator (YSI1500, USA) and globulimeter (SWLAB900+, USA). Statistical analyses were conducted to identify any differences in pre and post training data. Results Blood routine: RBC, Hb and HCT were increased on day 2 at altitude, decreased on day 5 and increased again on day 8. When altitude training was finished at week 4, the indexes above were higher than those on ascent to altitude. BUN appeared to be declining at altitude but remained within the normal range. SaO2 was decreased consistently and RHR (resting heart rate) increased gradually at week 1 at altitude. After 2 weeks, SaO2 was increased and RHR decreased. Urine indices were all normal. Weight was decreased by 2.48-6.88% for males and 2.22-5.58% for females. Bla, HR both decreased obviously with increased exercise intensity comparing initial with end stage. Conclusions The results suggested that the swimmers experienced a stress reaction at week 1 during 2366m altitude training and were shown to have been acclimatized to 2366m altitude after 1 week, recovering well and not being over-fatigued. Anabolism of protein decreased, catabolism of lipid increased and water was lost during the 2366m altitude training period suggesting that protein and water supplements should be provided and strength training emphasized.